Analysis on face recognition based on five different viewpoint of face images using MTCNN and FaceNet - Al-imran; Shams, Baniamin; Nasim, Faysal Islam (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.